Porphyromonas gingivalis PgFur Is a Member of a Novel Fur Subfamily With Non-canonical Function - Śmiga, Michał; Bielecki, Marcin; Olczak, Mariusz; Olczak, Teresa (Frontiers in Cellular and Infection Microbiology, 2019)
Porphyromonas gingivalis, a keystone pathogen of chronic periodontitis, uses ferric uptake regulator homolog (PgFur) to regulate production of virulence factors. This study aimed to characterize PgFur protein in regard to its structure-function relationship. We experimentally identified 5’ mRNA sequence encoding 171-amino-acid long PgFur protein in A7436 strain and examined this PgFur version as a full-length protein. Although purified PgFur protein did not bind to the canonical E. coli Fur box, the wild-type phenotype of the mutant pgfur strain was restored partially when expression of the ecfur gene was induced from the native pgfur promoter. The full-length PgFur protein contained one zinc atom per protein monomer, but did not bind iron, manganese, or heme. Single cysteine substitutions of CXXC motifs resulted in phenotypes similar to the mutant pgfur strain. The modified proteins were produced in E. coli at significantly lower levels, were highly unstable, and did not bind zinc. pgfur gene was expressed at higher levels in bacteria cultured for 24 h in the absence of iron and heme or under lower iron/heme availability for 10 h. No influence of high availability of Fe2+, Zn2+, or Mn2+ on pgfur gene expression was observed. To examine the influence of the unusual C-terminal lysine-rich region on potential PgFur function, two chromosomal mutant strains, allowing production of the protein lacking 4 (pgfur4aa) or 13 (pgfur13aa) C-terminal amino-acid residues of the native PgFur protein were constructed. The pgfur13aa strain showed phenotype typical for the mutant pgfur strain, but both the wild-type PgFur protein and its truncated version bound zinc with similar ability. pgfur mutant strain produced higher amounts of HmuY protein compared with the wild-type strain. Potential PgFur ligands, Fe2+, Mn2+, Zn2+, PPIX, or serum components, did not influence HmuY production in the pgfur mutant strain. The mutant pgfur4aa and pgfur13aa strains produced higher levels of HmuY protein. PgFur bound to the hmu operon promoter, further supporting involvement of this protein in regulation of the hmuY gene expression.